Routine hospital management of self-harm and risk of further self-harm: propensity score analysis using record-based cohort data. Issue 2 (22nd June 2017) - Steeg, S.; Emsley, R.; Carr, M.; Cooper, J.; Kapur, N.
Abstract : Background: The care received by people presenting to hospital following self-harm varies and it is unclear how different types of treatment affect risk of further self-harm. Method: Observational cohort data from the Manchester Self-Harm Project, UK, included 16 456 individuals presenting to an Emergency Department with self-harm between 2003 and 2011. Individuals were followed up for 12 months. We also used data from a smaller cohort of individuals presenting to 31 hospitals in England during a 3-month period in 2010/2011, followed up for 6 months. Propensity score (PS) methods were used to address observed confounding. Missing data were imputed using multiple imputation. Results: Following PS stratification, those who received a psychosocial assessment had a lower risk of repeat hospital attendance for self-harm than those who were not assessed [RR 0.87, 95% confidence interval (CI) 0.80–0.95]. The risk was reduced most among people less likely to be assessed. Following PS matching, we found no associations between risks of repeat self-harm and admission to a medical bed, referral to outpatient psychiatry or admission to a psychiatric bed. We did not find a relationship between psychosocial assessment and repeat self-harm in the 31 centre cohort. Conclusions: This study shows the potential value of using novel statistical techniques in large mental health datasets to estimate treatment effects. We found that specialist psychosocial assessment may reduce the risk of repeat self-harm. This type of routine care should be provided for all individuals who present to hospital after self-harm, regardless of perceived risk.